Hubungan Preeklamsia Pada Ibu Hamil Dengan Kejadian Asfiksia Neonatorum Di Rsud Bangkinang Tahun 2021-2022 - Jannah, Fitri Khafidhatul; Apriyanti, Fitri; Harmia, Elvira (Evidence Midwifery Journal, 2024)
Neonatal asphyxia is the failure of a newborn baby to breathe spontaneously and regularly, causing further problems. The emergence of asphyxia in babies with preeclamptic mothers is caused by high blood pressure causing reduced blood delivery to the placenta, this will reduce the supply of oxygen and food for the baby. As a result, the baby's development becomes slow, and intrauterine hypoxia occurs. The impact that occurs in babies with neonatal asphyxia will have an impact on the central nervous system, blood digestion, hypoxic ischemic encephalopathy, respiratory distress, heart failure, necrotizing, enterocolitis, acute kidney failure, lungs, entercolitis. Apart from that, it can also cause death in babies, the long-term impacts that will be experienced by children can result in mental retardation and neurological disorders. The aim of this research is to determine the correlation between preeclampsia in pregnancy and the incidence of Neonatal Asphyxia at Bangkinang District Hospital in 2021-2022. This research design uses quantitative research methods with a case control approach. Case samples were taken using total sampling technique and control samples using simple random sampling. The research was carried out at Bangkinang Regional Hospital. The research population of all newborns at Bangkinang District Hospital from 2021-2022 from January-September was 487 babies. There were 75 babies who experienced neonatal asphyxia and 75 babies who did not experience neonatal asphyxia. The research uses a secondary data checklist sheet. Univariate and Bivariate data analysis using the Chi-Squere test. These results indicate that there is a relationship between preeclampsia in pregnant women and the incidence of neonatal asphyxia obtained (P value 0.000) < (0.05). There is a relationship between preeclampsia in pregnant women and the incidence of neonatal asphyxia at Bangkinang District Hospital in 2021-2022 from January-September